2013
DOI: 10.1177/0961203313496339
|View full text |Cite
|
Sign up to set email alerts
|

Mestizos with systemic lupus erythematosus develop renal disease early while antimalarials retard its appearance: Data from a Latin American cohort

Abstract: Objectives To assess the predictors of time-to-lupus renal disease in Latin American patients. Methods SLE patients (n=1480) from GLADEL’s (Grupo Latino Americano De Estudio de Lupus) longitudinal inception cohort were studied. Endpoint was ACR renal criterion development after SLE diagnosis (prevalent cases excluded). Renal disease predictors were examined by univariable and multivariable Cox proportional hazards regression analyses. Antimalarials were considered time-dependent in alternative analyses. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 35 publications
(66 reference statements)
0
25
1
4
Order By: Relevance
“…Observational and cohort studies have demonstrated that antimalarials reduce the odds of developing LN in patients with SLE and are associated with a higher likelihood of a complete renal response to treatment and a reduced likelihood of developing end-stage kidney disease. [111][112][113][114] Corticosteroids. Corticosteroids, although almost universal in LN regimens, are associated with significant short-and longterm adverse effects.…”
Section: Treatmentmentioning
confidence: 99%
“…Observational and cohort studies have demonstrated that antimalarials reduce the odds of developing LN in patients with SLE and are associated with a higher likelihood of a complete renal response to treatment and a reduced likelihood of developing end-stage kidney disease. [111][112][113][114] Corticosteroids. Corticosteroids, although almost universal in LN regimens, are associated with significant short-and longterm adverse effects.…”
Section: Treatmentmentioning
confidence: 99%
“…Relative to Caucasians, African Americans and Hispanics develop more aggressive LN with earlier onset and poorer long-term renal outcomes (9). European ancestry is reportedly protective from LN in patients with SLE (10).…”
Section: Rheumatologymentioning
confidence: 99%
“…Another limitation was absence of SLE controls without LN. However, when comparing LN cases with SLE controls lacking LN, it is possible that some "non-nephropathy 12 (8)(9)(10)(11)(12)(13)(14)(15)(16) 18 (…”
Section: Downloaded Frommentioning
confidence: 99%
“…Contribuyen a la mortalidad la mala respuesta terapéutica, infecciones, compromiso cardiovascular y tromboembolismo. Los mestizos latinoamericanos presentan más frecuentemente NL graves y tempranas [4][5][6][7] . En Chile no disponemos de estudios de incidencia o prevalencia.…”
Section: Documento De Consenso De Las Sociedadesunclassified